Long-time oscillations in correlation of lysozyme solutions and the effects of antagonistic salt in external electric field light scattering. (4th March 2021) - Kang, Kyongok; Sadakane, Koichiro
Abstract: Lysozyme is a ubiquitous protein and enzyme that prevents the bacterial infections and maintains the catalytic balance in majority of biological fluids. However, it often causes problems at higher concentrations. In particular, the build up of lysozyme engaged with other protein interactions initiates severe disorders in most mammalian cells, such as the formation of harmful aggregates in the nervous system and the loss of connectivity in rheumatism. To understand such complex behaviors with respective to the catalytic activity of the enzyme, the lysozyme solution and the effect of hydrophobic antagonistic salt (NaBPh4) are explored in-vitro, in their relaxation behaviors. Here, we used, both normal dynamic light scattering and home-built in situ AC external electric field light scattering. As results, the fast and slow-mode (with stretched) relaxations are observed in the conventional dynamic light scattering (without an electric field). The results are particularly noteworthy under a low electric field, with robust long-time oscillations, in the scattered intensity correlation function. In addition, the effective interactions are explored by varying the ionic strength of the antagonistic salt: The oscillations are less pronounced, but still clearly represent the 'underdamped' motions. Overall, reductions of the relaxations are shown with the applied electric field, with a maximum relaxation occuring at 1mM. In contrast, monotonic decreases of the relaxation rates are shown above 10 mM. Thus, the lysozyme exhibits a charged carrier, responding to ultimate low-frequency oscillations in the scattered correlations. The fit function of long-time oscillation in correlation is presented by an alternating cosine function with a phase, which is related to its possible dynamic elelctrophoretic mobility.